#### Answer

$\frac{4}{13}$

#### Work Step by Step

$\frac{9}{13}$ -$\frac{5}{13}$=$\frac{9-5}{13}$ =$\frac{4}{13}$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

$\frac{4}{13}$

$\frac{9}{13}$ -$\frac{5}{13}$=$\frac{9-5}{13}$ =$\frac{4}{13}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.